270 Evidence for the amnion-fetal gut-microbial axis in late gestation beef calves. (30th November 2020) - Hummel, Gwendolynn; Woodruff, Kelly; Austin, Kathleen; Smith, Travis; Cunningham, Hannah
Abstract: As the most immediate membrane surrounding the fetus, the amnion carries great potential as a microbial source of inoculation for the calf's rumen microbiome. We hypothesize the calf is exposed to a microbial source prior to birth, and that the amnion plays an essential role in inoculation prepartum. Our objective was to isolate and identify microbes of the amniotic fluid and vaginal canal during late gestation and compare these populations to rumen fluid and meconium of newborn calves. Vaginal (VAG) and amniotic fluid (AF) samples were obtained from multiparous beef cows (n = 10) 10 days prior to their expected calving date. Rumen fluid (RF) and meconium (MEC) samples were obtained from each newborn calf immediately following parturition. Microbial DNA was isolated and purified utilizing the QIAmp DNA Stool Minikit (Qiagen) for amplicon 16S rRNA sequencing. All analysis was performed in QIIME2. Alpha-diversity was not different between MEC and AF (q ≥ 0.09) under any metric, but MEC and VAG differed under Faith's Phylogenetic Diversity (q = 0.03). The MEC, AF, and VAG all differed in beta-diversity (q = 0.003). The degree of similarity between AF and MEC may indicate the AF plays a crucial role in the colonization of the fetal gut prepartum. Each of these lines of evidence outline fundamental aspects of the unfolding amnion-fetal gut-microbial axis, and provide key targets for future research into rumen development and the manipulation of feed efficiency in beef calves.